Field of creative culture: a study of creative movement and innovation of terracotta culture in Jatiwangi, Indonesia - Ekomadyo, Agus S.; Wijaya, Nurrohman; Vardhani, Vera J.; Maulana, Annas T.; Suhendar, Hernadi; Susanto, Vanessa (Creativity Studies, 2023)
Although the creative city concept has received much criticism, the creative movement still occurs to fight for a better city. The decline in the terracotta tile business in Jatiwangi, Majalengka Regency, West Java, Indonesia, has triggered a creative movement to revitalize their identity through the Terracotta City movement. By combining Mihaly Csikszentmihalyi’s field of creativity and Pierre Bourdieu’s cultural capital, this study is carried out to reveal the creative culture of terracotta tile entrepreneurs in Jatiwangi and its relation to the movement. It is found that entrepreneurs’ creative culture is dominantly stimulated by economic capital, and then it is transformed into cultural capital. Innovations are only made, if the market share is clear since it bears economic risks. However, social capital has a role in transforming entrepreneurs’ economic and cultural capital to accept innovation and product diversification. This study also reveals that entrepreneurs as adopters intend to initiate innovation and diversification of terracotta products. However, within the framework of innovation, it shows that creative culture plays a role in incorporating aspects of humanity into innovation activities by giving innovation efforts to represent human beings.